PELAKSANAAN SENAM PAGI DI SDN 153/VI RANTAU PANJANG X KECAMATAN TABIR - Hamdan, Muhammad (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract This research, there was a problem with the implementation of morning exercise which was not running well and smoothly. There are several factors that influence students, namely intrinsic motivation factors and extrinsic motivation factors that occur in students. This resulted in the exercise not running. This type of research is descriptive. The population in this study was 172 students at SDn 153/VI Rantau Panjang X, Tabir District. With samples taken using statistical random sampling technique, the sample consisted of 49 students. In this research, the type of data is primary data, namely data originating from distributing questionnaires, data collected through questionnaires and analyzed using percentages. The results of this research are that for the student intrinsic motivation variable, an achievement level of 80.70% was obtained. This means that students' understanding of their own intrinsic motivation for carrying out morning exercise at SDN 153/VI Rantau Panjang X, Tabir District is in a good classification. Likewise, for the student extrinsic motivation variable, an achievement level of 80.78% was obtained. This means that students' understanding of the external motivation that they apply to the implementation of morning exercise is also in a good classification. It is recommended that the school be more diligent and active in motivating students so that the morning exercise can run well as we hope. Keywords: Implementation exercise morning